Improving Affective Behaviors in MLS Students. - ALPAUGH, TAMERA; ROMAIN, CHARLOTTE; WIESNER, STEPHEN (Clinical Laboratory Science)
Dealing with professional affective behaviors of students during the clinical experience requires significant effort by clinical coordinators. It can have lasting negative impacts on students as well as on the relationship between a laboratory science program and its clinical affiliates. Reduction of effort required to address these issues is in the best interest of the program, the clinical affiliate, and--most importantly--the student. To reduce events that require attention by the clinical coordinator and to improve awareness, the University of Minnesota medical laboratory science program implemented a multipoint approach to educate students about affective behaviors. A series of curricular components were developed based on the university's technical standards, including peer evaluations, preceptor evaluations, weekly postlaboratory reflections, course director evaluations of student behavior, student selfassessment, student self-assessment with faculty feedback, and individual student discussions to improve affective behaviors of the graduates. Over the course of 3 years, these efforts reduced the number of events that required the attention of the clinical coordinator by greater than 50%. Significant events that required remediation by the student were relatively unchanged but continued to represent only about 5% of the total number of events recorded. A multi-point approach can help improve affective outcomes for students and reduce effort by clinical coordinators and affiliate preceptors to address adverse affective events.